29. Trinidad - (:unkn) unknown (My University, 2010)
An aerial view of the Queen's Park Savannah in Port of Spain, early 1900 to the 1950s. In the distance, the Port of Spain harbour can be seen.
Colour: Black and white (print); Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Port of Spain; Trinidad and Tobago--Aerial Views; Harbors--Trinidad and Tobago; Savannas--Trinidad and Tobago; Queen's Park Savannah (Port of Spain)